PRODUK PEMIKIRAN HUKUM ISLAM DAN PROBLEMATIKANYA DI INDONESIA - Hannani, Hannani (DIKTUM: Jurnal Syariah dan Hukum, 2010)
This article studies the products of Islamic legal thought and their problems in Indonesia. The products of Islamic legal thought are the products of ijtihad of Islamic scholars (‘ulama) on Islamic laws concerning the activities (a’mal) of human beings. The primary sources of the products of Islamic legal thought are alquran and al-Hadits, while their secondary sources are logical reasoning (al-ra’yu). The application of the products of Islamic legal thought in Indonesia implicitly raises problems, yet explicitly it raises no problems as they are implemented in accordance with Indonesian constitution. Nevertheless, what escapes from our constitution is the criminal law (jinayat) that contains the punishment (hadd) such as cutting off hands for thieves. In this case, the practise of imprisoning the thieves is essentially in harmony with Islamic law.